The sedimentation theory of cultural time and space: the present is embedded in the past - St. Clair, Robert N. (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Linear time is a metaphor based on the concept of Euclidean space (St. Clair, 2006). One of the difficulties associated with this concept of time is that although it incorporates change as movement from one steady-state to another, it cannot account for the process that motivates that change of time within the same cultural space. A more insightful model of temporal and spatial change can be found in the metaphor of the “Archeology of Knowledge” (Foucault, 1969). A modification of this metaphor can be found in the sedimentation theory of time in space which envisions time as the accumulation of social practices layered in cultural space. It is argued that the present is embedded in the cultural past. The dynamics of change in a cultural space occurs in the co-present, a place where the reconstructed past is linked with the co-present. It is in this co-present space that the social construction of cultural space takes place. Some events are retained and defined as belonging to the past and are designated as the old-present; other events are modified, redefined, or restructured in the present and function as the new-present. It is this social and cultural habitus (Bourdieu, 1977, 1984) that explains how meanings are contextualized and interpreted within the co-present. Rather than viewing culture as a superorganic entity, a collective consciousness, existing outside of human experience, culture is considered to be a set of practices, habits, and recipes for daily interaction emerging from the experiences of everyday life. It is by using the past to make sense of the present that the social construction of culture comes into existence (Mehan and Wood, 1975). Such practices are internalized through daily interaction in the form of social scripts (St. Clair, Thomé-Williams, and Su, 2005) and other forms of structuration (Giddens, 1984). Cultural change involves the retaining of some cultural practices along with the modification, revision, and re-invention of events in the co-present. Just as the present is embedded in the past, the future is embedded in the present.